Scenario planning as approach to improve the strategic performance of multinational corporations (MNCs) - Ahmad Nasser Abuzaid (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
The primary purpose of this study was to explore the relationship between scenario planning and strategic performance. The data was collected from 121 Multinational corporations operating in Jordan by using a questionnaire. Pearson correlation and the partial least squares (PLS) methodology for factor analysis and path modelling was used to test the study hypotheses. The study found a positive and statistically significant relationships between scenario planning and the four components of strategic performance: financial performance, customer performance, learning and growth, and internal business processes. Based on these findings, the study recommends that managers should apply scenario planning practices to enhance the levels of strategic performance in their companies. Additionally, managers should raise the awareness of their employees regarding the importance of both scenario planning and strategic performance. Moreover, managers should provide their employees with adequate training courses in relation to acquire the knowledge and build their skills in the field of scenario planning. Finally, managers should use the diagnostic instruments that developed by previous research to assess a company's strategic performance and scenario planning practices, identify managerial practices that need to be implemented or improved, and determine the resources that might realistically be required to build a better scenario planning process and promote strategic performance. Much more research and studies need to be performed in this budding subject. Links among scenario planning and another organizational topics and outcomes need to be searched.
Keywords: M10; C53; O21; F23; 650; scenario; scenario planning; strategic performance; MNCs; Jordan